Biological fiber composite material for reinforcing paper cultural relics and preparation method of biological fiber composite material

Through the composite material of nanocellulose and natural polymer, combined with antioxidants, ultraviolet shielding agents and self-healing microcapsules, multi-layer progressive coating and vacuum-assisted penetration process are used to solve the lack of transparency and compatibility in paper cultural relics reinforcement. The problems of poor performance, limited anti-aging performance, high maintenance cost and poor permeability have achieved traceless, high transparency, self-repairability and deep reinforcement protection effects.

CN119411428APending Publication Date: 2025-02-11NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411655477.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art has problems such as insufficient transparency, poor compatibility, limited anti-aging performance, high maintenance costs and poor permeability of the reinforcement layer in the reinforcement, which is difficult to meet the needs of long-term protection and traceless reinforcement.

Method used

Using composite materials of nanocellulose and natural polymers, combined with antioxidants, UV shielding agents and self-healing microcapsules, a protective layer with high transparency, self-healing and deep reinforcement is formed through multiple layers of progressive coating and vacuum-assisted penetration process. .

Benefits of technology

It achieves traceless reinforcement, improves the mechanical strength and anti-aging properties of the paper, extends the storage time of cultural relics, reduces maintenance costs, and ensures the stability and deep protection of the reinforcement layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411428A_ABST
    Figure CN119411428A_ABST
Patent Text Reader

Abstract

The invention relates to the field of cultural relic protection, and discloses a biological fiber composite material for reinforcing paper cultural relics, which comprises nano cellulose accounting for 5-20% of the total mass of the composite material; the natural polymer bonding base material accounts for 10-30% of the total mass of the composite material; an antioxidant accounting for 0.1-2% of the total mass of the composite material; the ultraviolet screening agent accounts for 0.5-5% of the total mass of the composite material; and the self-repairing microcapsule accounts for 1-10% of the total mass of the composite material. The transparent composite material with high mechanical strength is prepared from the high-strength nano cellulose and the biocompatible natural polymer, and is used for reinforcing the paper cultural relics and keeping the appearance and texture of the paper cultural relics. Compared with a traditional material, no obvious trace exists, the physical performance of paper is remarkably improved, and the problems of poor transparency and reinforcing trace are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cultural relics protection, in particular to a biofiber composite material for reinforcing paper cultural relics and a preparation method thereof. Background Art

[0002] Paper cultural relics are an important carrier of human civilization due to their unique historical and cultural value. However, due to the fragility of paper fiber structure and the organic composition of paper itself, paper cultural relics are extremely vulnerable to environmental factors, such as oxidation, ultraviolet radiation, humidity changes, etc. These factors will accelerate the aging, discoloration, and brittleness of paper fibers, and even cause irreversible damage to cultural relics. Therefore, the reinforcement and protection of paper cultural relics is of great significance in the field of cultural relic restoration and long-term preservation. Traditional paper reinforcement methods mainly use a layer of polymer or other reinforcement materials coated on the surface of the cultural relic to increase the strength of the paper and delay aging. However, the existing technology has many shortcomings in practical applications, and it is difficult to meet the needs of long-term protection and traceless reinforcement of paper cultural relics, which are specifically reflected in the following aspects:

[0003] Insufficient transparency and compatibility of reinforcement materials:

[0004] Traditional reinforcement materials mostly use chemical synthetic polymers, such as polyvinyl alcohol, polyurethane and silicone. These materials have high strength to a certain extent and can improve the tear resistance and bending resistance of paper. However, this type of material has poor transparency and is easy to form obvious traces of the reinforcement layer on the surface of the paper, which directly affects the original appearance and visual effect of the paper cultural relics. For paper cultural relics with a long history and high aesthetic value, any obvious traces of reinforcement will weaken their historical texture and damage their cultural value. In addition, the molecular structure of chemical polymers lacks good compatibility with paper fibers. After coating, it will destroy the flexibility of the paper and increase the risk of embrittlement between fibers. Over time, the reinforcement layer may even crack, peel off, and other problems, resulting in a decrease in the protective effect. Therefore, the reinforcement materials in the prior art are difficult to meet the requirements of tracelessness and compatibility for the reinforcement of cultural relics.

[0005] Lack of effective anti-aging protection limits the shelf life of paper:

[0006] During the long-term preservation process, paper cultural relics are extremely susceptible to oxidation and light exposure, causing yellowing and brittleness, which reduces their preservability. Existing reinforcement materials usually lack effective antioxidant and UV shielding components. Even if the paper is reinforced, the material itself is still susceptible to oxidation and UV radiation, causing paper cultural relics to gradually fade and become fragile in structure. Some technologies attempt to introduce anti-aging additives such as antioxidants or UV absorbers into reinforcement materials, but these ingredients are not compatible with polymers, which may affect the uniformity and stability of the material and make the reinforcement layer prone to delamination and separation. In humid or high temperature environments, these components may also undergo chemical changes and lose their original anti-aging effects. The deficiencies of existing technologies in anti-aging protection mean that paper still faces the risk of aging after reinforcement, making it difficult to truly extend the preservation time of cultural relics.

[0007] Lack of self-repairing capability leads to high maintenance costs for the reinforcement layer:

[0008] Due to the thinness and flexibility of the structure, paper cultural relics often suffer from cracks, peeling and other damages in the reinforcement layer after being subjected to external forces, environmental fluctuations or aging of the material itself. Traditional reinforcement materials are mostly rigid polymers that lack self-repairing functions. Once damaged, they can only rely on re-coating or repair. This not only increases the risk of continuous faults in the reinforcement layer, affecting its long-term use effect, but also causes secondary intervention in the cultural relics, bringing great difficulties to subsequent maintenance work. Frequent maintenance and repair not only cause unnecessary physical interference to the cultural relics themselves, but also easily cause cumulative damage, increasing the complexity and cost of protection. Therefore, existing reinforcement materials cannot self-repair, have high maintenance costs, and are difficult to meet the needs of long-term protection of paper cultural relics.

[0009] The reinforcement material has poor permeability, making it difficult to achieve deep reinforcement:

[0010] Traditional paper reinforcement methods are mostly single-layer surface coatings, which cannot deeply penetrate into the internal fiber structure of the paper, resulting in the reinforcement layer being mainly concentrated on the surface, which is easily affected by changes in environmental temperature and humidity and may fall off or crack. This surface coating method has a relatively shallow reinforcement effect, making it difficult to enhance the stability of the internal structure of the paper, and cannot meet the needs of deep reinforcement for long-term preservation of paper. At the same time, due to the concentrated effect of surface reinforcement, the coating layer is often unevenly adhered, and it is easy to produce unevenly distributed thick and thin layers on the surface of the paper, making the reinforcement effect uneven and accelerating the aging process of the paper. The existing technology lacks effective penetration means, resulting in the difficulty of the reinforcement material penetrating into the microstructure of the paper fiber and forming a stable reinforcement structure. Especially in the case of long-term storage or high-frequency use, the reinforcement layer is prone to lose adhesion, and it is impossible to achieve comprehensive protection of the cultural relic structure.

[0011] Therefore, the present invention proposes a biofiber composite material for reinforcing paper cultural relics and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention

[0012] In view of the shortcomings of the prior art, the present invention provides a bio-fiber composite material for reinforcing paper cultural relics and a preparation method thereof, aiming to solve the problems of traditional reinforcement materials such as insufficient transparency, poor compatibility, limited anti-aging performance, high maintenance cost, and insufficient permeability of the reinforcement layer.

[0013] To achieve the above purpose, the present invention is implemented through the following technical scheme: a biofiber composite material for reinforcing paper cultural relics, the composite material comprising the following components:

[0014] Nanocellulose, accounting for 5-20% of the total mass of the composite material, and the particle size of the nanocellulose is 20-100 nanometers;

[0015] A natural polymer bonding substrate, accounting for 10-30% of the total mass of the composite material, wherein the natural polymer bonding substrate comprises a mixture of chitosan and gelatin, and the mass ratio of chitosan to gelatin is 2:1;

[0016] An antioxidant, accounting for 0.1-2% of the total weight of the composite material, wherein the antioxidant comprises catechin and / or ferulic acid;

[0017] An ultraviolet shielding agent, accounting for 0.5-5% of the total mass of the composite material, wherein the ultraviolet shielding agent comprises titanium dioxide nanoparticles and lignin;

[0018] The self-repairing microcapsules account for 1-10% of the total mass of the composite material. The self-repairing microcapsules wrap polysiloxane and the size of the self-repairing microcapsules is 0.5-1 micron.

[0019] Preferably, the mass ratio of catechin to ferulic acid in the antioxidant is 1:1 to 3:1.

[0020] Preferably, the particle size of the titanium dioxide nanoparticles in the ultraviolet shielding agent is 10-50 nanometers, and the mass percentage of the lignin in the composite material is 0.5-2%.

[0021] Preferably, a method for preparing a biofiber composite material for reinforcing paper cultural relics comprises the following steps:

[0022] (1) ultrasonically dispersing 5-20% of nanocellulose in deionized water for 15-30 minutes to prepare a nanocellulose dispersion;

[0023] (2) adding 10-30% chitosan and gelatin in a mass ratio of 2:1 into the nanocellulose dispersion and stirring until it is uniformly dissolved;

[0024] (3) adding 0.1-2% of an antioxidant and 0.5-5% of an ultraviolet shielding agent to the mixed solution of step (2), and subjecting the mixture to mechanical stirring and ultrasonic treatment for 10 minutes to obtain a uniformly dispersed mixed solution;

[0025] (4) adding 1-10% of self-repairing microcapsules to the mixed solution of step (3), stirring at a low speed for 5-10 minutes to uniformly disperse the self-repairing microcapsules in the mixed solution, and obtaining a composite material solution;

[0026] (5) Add an appropriate amount of ethanol or propylene glycol to adjust the viscosity of the mixed solution in step (4) to a fluidity suitable for coating.

[0027] Preferably, in step (1), the nanocellulose is ultrasonically dispersed in deionized water for 20 minutes at a mass fraction of 5-20%, and has high dispersion uniformity; the antioxidant in step (3) is a combination of 0.5% by mass of catechins and 0.3% by mass of ferulic acid, and the ultraviolet shielding agent is a combination of 1% by mass of titanium dioxide and 1% by mass of lignin.

[0028] Preferably, a method for reinforcing paper cultural relics comprises the following steps:

[0029] The composite material solution is coated on the surface of paper layer by layer with a thickness of 0.3-0.5 microns to form a multi-layer progressive coating, and each layer is dried at low temperature after coating;

[0030] Placing the paper artifact in a vacuum environment, wherein the vacuum pressure is controlled at 50-100 kPa, and using a vacuum-assisted infiltration process to allow the composite material solution to infiltrate into the paper structure;

[0031] Each coating layer is dried at a temperature not exceeding 40°C for 30 minutes to cure the composite material layer by layer to obtain a multi-layer reinforcement effect.

[0032] Preferably, the multi-layer progressive coating comprises 3-5 layers of coating, the nanocellulose concentration of the composite material solution in each layer decreases layer by layer, and the outermost layer is a composite material solution with high transparency to improve the transparency of the final coating.

[0033] Preferably, the vacuum-assisted infiltration process includes maintaining a vacuum environment of 50-100 kPa for 5-15 minutes, so that the composite material solution enters the gaps between paper fibers under the action of vacuum to form a tightly combined reinforcement structure.

[0034] Preferably, a paper cultural relic reinforcement system comprises the following devices:

[0035] A biofiber composite material preparation device for preparing a biofiber composite material containing nanocellulose, natural polymer, antioxidant, UV shielding agent and self-repairing microcapsule according to the steps of claims 1 to 4;

[0036] Environmental control device, used to provide constant temperature conditions of 20-25°C and constant humidity conditions of 50-60% to prevent the paper from being affected by environmental changes during the reinforcement process;

[0037] A coating device, used to coat the composite material solution on the paper surface layer by layer with a thickness of 0.3-0.5 microns;

[0038] Vacuum-assisted penetration device, used to place paper artifacts in a vacuum environment of 50-100 kPa to allow the composite material solution to evenly penetrate the paper structure;

[0039] Low-UV lighting device, used for low-UV lighting of paper artifacts during the reinforcement process.

[0040] The present invention provides a biofiber composite material for reinforcing paper cultural relics and a preparation method thereof. It has the following beneficial effects:

[0041] 1. The present invention adopts a composite design of nanocellulose and natural polymers. By combining high-strength nanocellulose with natural polymers with good biocompatibility, the composite material has excellent mechanical strength and high transparency, thereby reinforcing paper cultural relics while maintaining the integrity of their appearance and the authenticity of their texture. Compared with the polymer reinforcement materials commonly used in the prior art, which easily leave obvious reinforcement marks on the surface of paper, damaging the visual beauty and historical texture of cultural relics, the composite structure of the present invention achieves the effect of traceless reinforcement, which not only improves the strength and toughness of paper in terms of physical properties, but also retains the natural appearance of cultural relics, solving the problems of poor transparency, obvious reinforcement marks, and decreased flexibility after reinforcement of traditional materials, and provides a better solution for the protection of paper cultural relics.

[0042] 2. The present invention introduces a synergistic system of antioxidants and UV shielding agents into the composite material, so that the reinforcement layer has dual protection of anti-oxidation and anti-ultraviolet, thereby effectively slowing down the natural aging rate of paper cultural relics and extending the preservation time of cultural relics. Compared with the materials in the prior art that lack effective antioxidant and UV shielding functions, paper is still susceptible to oxidation, light-induced fading, yellowing and embrittlement after reinforcement. The present invention forms a composite reinforcement material with efficient protection by mixing natural antioxidant ingredients (such as catechins, ferulic acid) and UV shielding ingredients (such as titanium dioxide nanoparticles and lignin) in a scientific proportion, thus overcoming the shortcomings of traditional materials in anti-aging. This solution can not only effectively protect the fiber structure of paper cultural relics in harsh environments, but also enable the paper to maintain its color and structural stability when exposed to light for a long time, providing more comprehensive protection for cultural relics.

[0043] 3. The present invention adds self-healing microcapsule technology to the composite material. Through the design of microcapsules wrapped with polysiloxane, the reinforcement layer can automatically release repair components to fill the damaged area when it is damaged by tiny cracks, wear or temperature and humidity fluctuations, thereby extending the service life of the reinforcement layer and reducing the need for later maintenance of cultural relics. Compared with the prior art, if traditional reinforcement materials crack or fall off during use, they usually need to be reinforced again, which not only increases the number of interventions on cultural relics, but also easily causes discontinuity and shortened service life of the reinforcement layer. The present invention uses the design of self-healing microcapsules. When cracks or slight damage appear in the reinforcement layer, the microcapsules spontaneously release polysiloxane to fill and repair the cracks, thereby achieving self-repair of the reinforcement layer, greatly improving the durability and stability of the reinforcement layer, reducing later maintenance work, and ensuring that cultural relics are effectively protected for a long time.

[0044] 4. The present invention combines multi-layer progressive coating and vacuum-assisted infiltration technology to make the composite material penetrate layer by layer into the internal microstructure of the paper, thereby achieving deep reinforcement and comprehensive coverage of paper cultural relics at different levels, effectively improving the adhesion and uniformity of the reinforcement material, and ensuring the overall stability of the paper fiber structure. Compared with the single-layer surface coating method in the prior art, the reinforcement effect is often limited by the unevenness of the paper surface, making it difficult to penetrate into the internal structure of the paper, and the reinforcement layer is prone to fall off or cracking. The present invention controls the coating thickness and material concentration by layer, so that the composite material penetrates layer by layer and is evenly distributed in the fiber structure of the paper, and uses vacuum-assisted infiltration technology to remove the gas in the micropores of the paper, so that the composite material is more closely combined with the paper structure, thereby forming a deeper reinforcement effect. This process significantly improves the permeability and adhesion of the composite material, ensures that the reinforcement layer is not easy to fall off, solves the problem that traditional reinforcement materials cannot penetrate into the paper fibers and have insufficient adhesion, and achieves deep protection and comprehensive reinforcement of the paper cultural relic structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Flow chart of the preparation method of biofiber composite materials for reinforcing paper cultural relics. DETAILED DESCRIPTION

[0046] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Please see attached Figure 1 :

[0048] Example:

[0049] Example 1: Example of innovative components within the range of values ​​and example of parameters within the range of values ​​in the preparation process

[0050] Material ratio and preparation process

[0051] Ingredients ratio:

[0052] Nanocellulose: 15% of the total mass, with a particle size of 50 nanometers, improving transparency and strength;

[0053] Natural polymer bonding substrate (chitosan: gelatin = 2:1): 20% of the total mass, to improve compatibility with paper fibers;

[0054] Antioxidants (catechins and ferulic acid, mass ratio of 1.5:1): 1% of the total mass, delaying the oxidative aging of paper;

[0055] UV shielding agent (titanium dioxide and lignin, mass ratio of 1:1): 2% of the total mass, reducing fading and embrittlement caused by UV rays;

[0056] Self-healing microcapsules: 5% of the total mass, encapsulated polysiloxane, 0.8 micron in size, enhanced self-healing ability.

[0057] Preparation method:

[0058] (1) Nanocellulose was dissolved in deionized water and dispersed by ultrasonic for 20 min to ensure uniform distribution.

[0059] (2) Chitosan and gelatin were added into the nanocellulose dispersion in a ratio of 2:1 and stirred until completely dissolved to form a stable matrix.

[0060] (3) Antioxidants and UV shielding agents were added in proportion, mechanically stirred and ultrasonically treated for 10 minutes to ensure that the ingredients were evenly dispersed.

[0061] (4) Slowly add the self-healing microcapsules into the mixture and stir at a low speed for 5 minutes to prevent breakage.

[0062] (5) Add an appropriate amount of ethanol to adjust the viscosity to obtain a composite material solution suitable for coating.

[0063] Reinforcement Application:

[0064] The composite material solution was evenly coated on the surface of the paper artifact with a thickness of 0.4 microns, and three layers were applied layer by layer. Each layer was dried at low temperature (40°C) and a 50kPa vacuum penetration process was used to allow the material to penetrate deeply into the paper fibers.

[0065] Summary of Examples

[0066] This embodiment uses the values ​​within the optimal range in terms of composition and process parameters, and the prepared composite material has high transparency, strong anti-aging properties, and good penetration depth. The appropriate concentration of self-repairing microcapsules enhances the durability of the reinforcement layer and achieves excellent protection effect without destroying the paper structure.

[0067] Example 2: Examples of innovative components below the range and examples of parameters below the range in the preparation process

[0068] Material ratio and preparation process

[0069] Ingredients ratio:

[0070] Nanocellulose: 4% of the total mass, particle size 15 nanometers;

[0071] Natural polymer bonding substrate (chitosan: gelatin = 1:1): 8% of the total mass;

[0072] Antioxidants (catechins only): 0.05% of the total mass;

[0073] UV shielding agent (titanium dioxide only): 0.4% of the total mass;

[0074] Self-healing microcapsules: 0.8% of the total mass, 0.3 microns in size.

[0075] Preparation method:

[0076] (1) 4% nanocellulose was added into deionized water and dispersed by ultrasonic for 10 minutes.

[0077] (2) Add 8% chitosan and gelatin in a ratio of 1:1 into the dispersion and stir until initially mixed.

[0078] (3) Antioxidants and UV shielding agents were gradually added and mechanically stirred for 5 minutes without ultrasonic treatment.

[0079] (4) Add the self-healing microcapsules and stir at low speed for 3 minutes, and finally adjust the viscosity.

[0080] Reinforcement Application:

[0081] The coating thickness is controlled at 0.2 microns, the drying temperature does not exceed 30°C, two layers of coating are performed, and the vacuum penetration time is controlled at 5 minutes.

[0082] Summary of embodiments:

[0083] In this embodiment, the contents of nanocellulose, antioxidant, UV shielding agent and self-repairing microcapsule are all lower than the recommended range, resulting in the reinforcement layer strength and aging resistance being inferior to those in Example 1. Although the transparency is slightly improved, the penetration depth and durability are insufficient, affecting the overall reinforcement effect.

[0084] Result analysis:

[0085] When the concentration of ingredients is lower than the recommended range, the anti-aging ability is weak and the color is easily faded after ultraviolet radiation. When the concentration of self-repairing microcapsules is lower than the recommended concentration, the self-repairing effect is significantly reduced and the adhesion of the reinforcement layer is reduced.

[0086] Example 3: Examples of innovative components with values ​​higher than the range and examples of parameters in the preparation process with values ​​higher than the range

[0087] Material ratio and preparation process

[0088] Ingredients ratio:

[0089] Nanocellulose: 25% of the total mass, particle size 120 nanometers;

[0090] Natural polymer bonding substrate (chitosan: gelatin = 3:1): 40% of the total mass;

[0091] Antioxidants (catechins and ferulic acid, mass ratio 3:1): 3% of the total mass;

[0092] UV shielding agent (nano titanium dioxide and lignin, mass ratio of 1.5:1): 7% of the total mass;

[0093] Self-healing microcapsules: 12% of the total mass, 1.5 microns in size.

[0094] Preparation method:

[0095] (1) Nanocellulose was dispersed in deionized water and ultrasonically dispersed for 35 min.

[0096] (2) Add chitosan and gelatin mixture in a ratio of 3:1 and stir to dissolve.

[0097] (3) Antioxidant and UV shielding agent were added, mechanically stirred and ultrasonically treated for 15 minutes.

[0098] (4) After adding the self-repairing microcapsules, stir at low speed for 10 minutes.

[0099] Reinforcement Application:

[0100] The coating thickness was 0.7 μm, the drying temperature was 45° C., and after 5 layers of coating, vacuum penetration treatment was performed for 10 minutes.

[0101] Summary of embodiments:

[0102] This embodiment improves the anti-aging and self-repairing properties through a high concentration ratio, but the thicker coating and larger particle size of nanocellulose slightly reduce the transparency, and due to the excessive amount of nanocellulose, the flexibility of the composite material is reduced, affecting the overall appearance of the cultural relic.

[0103] Result analysis:

[0104] High concentrations of ingredients increase aging resistance and penetration depth, but also affect the transparency and flexibility of the coating, and drying at higher temperatures may cause paper deformation. Therefore, moderate control of ingredient concentration is the key to ensuring material transparency and reinforcement performance.

[0105] Comparative experiment:

[0106] Comparative experiment 1: Comparison between the prior art without the composite design of nanocellulose and natural polymer and the technical solution of the present invention

[0107] Purpose:

[0108] The effect of the composite design of nanocellulose and natural polymers in improving the transparency, compatibility and flexibility of the reinforcement material was evaluated, and the advantages of the design of the present invention in protecting the integrity of the appearance of paper cultural relics were verified.

[0109] Experimental process:

[0110] Material ratio:

[0111] Comparative Example 1: Using a conventional polyvinyl alcohol (PVA) solution as a reinforcement material without nanocellulose and natural polymers. The mass fraction of polyvinyl alcohol is 30%, which is dissolved in deionized water to obtain a uniform solution.

[0112] Example 1: A composite design using nanocellulose and natural polymer bonding substrate, wherein nanocellulose accounts for 15% of the total mass (particle size is 50 nanometers), the natural polymer bonding substrate accounts for 20% of the total mass (the mass ratio of chitosan to gelatin is 2:1), and the remaining components and process parameters are consistent with Example 1.

[0113] Preparation and reinforcement:

[0114] Comparative Example 1: The polyvinyl alcohol solution is evenly coated on the surface of the paper to form a single-layer coating with a thickness of 0.4 microns, and dried naturally. After each layer is dried, the process is repeated twice to form three layers of coating.

[0115] Example 1: According to the composite formula and steps of Example 1, the material is coated on the surface of paper, 3 layers are coated layer by layer, each layer is 0.4 microns thick, and then coated again after drying, and the low temperature is controlled at 40°C.

[0116] Test items:

[0117] Transparency test: The light transmittance is used to measure the light transmittance of paper to reflect the transparency of the coating.

[0118] Flexibility test: The reinforced paper is subjected to a bending test to observe the cracks and breaks of the coating during the bending process.

[0119] Compatibility test: Observe the coated surface for obvious reinforcement marks to evaluate the non-marking property and adhesion of the coating.

[0120] Experimental data:

[0121] Test items Embodiment 1 (present invention) Comparative Example 1 (conventional polyvinyl alcohol) Transparency (% light transmittance) 0.95 0.78 Flexibility high middle Compatibility No obvious signs of reinforcement Obvious traces of coating

[0122] Experimental summary:

[0123] Comparative Example 1 of traditional polyvinyl alcohol material showed low transparency (78% light transmittance), and left obvious coating marks on the surface of the paper after reinforcement, and had poor flexibility, and was prone to cracking during bending. The composite design of nanocellulose and natural polymer in Example 1 of the present invention greatly improved the transparency (up to 95% light transmittance) and flexibility of the reinforcement material, and the coating showed a traceless effect after reinforcement, and was highly compatible with paper fibers. This shows that the composite design of nanocellulose and natural polymer can achieve effective reinforcement without affecting the original appearance of the cultural relics, and is an ideal choice for the protection of paper cultural relics.

[0124] Comparative experiment 2: Comparison between the prior art without the introduction of a synergistic system of antioxidants and UV shielding agents and the technical solution of the present invention

[0125] Purpose:

[0126] To verify the effect of the synergistic system of antioxidants and UV screeners on improving the anti-aging properties in composite materials and to evaluate its effectiveness in slowing down the fading and embrittlement of paper artifacts.

[0127] Experimental process:

[0128] Material ratio:

[0129] Comparative Example 2: does not contain antioxidants and UV shielding agents, only uses nanocellulose (15%) and natural polymer bonding substrate (20%, chitosan and gelatin in a ratio of 2:1), and other components and processes are consistent with Example 1.

[0130] Example 1: Nanocellulose (15%, particle size 50 nanometers), natural polymer bonding substrate (20%), and added with 1% antioxidant (catechin and ferulic acid, mass ratio 1.5:1) and 2% UV shielding agent (titanium dioxide and lignin, mass ratio 1:1).

[0131] Preparation and reinforcement:

[0132] Comparative Example 2 and Example 1 were prepared and coated according to their respective proportions, the coating thickness was controlled at 0.4 μm, 3 layers were coated layer by layer, and each layer was dried at 40°C.

[0133] After coating, the samples were placed in an accelerated aging chamber for 72 hours of alternating cycles of light and humidity to simulate a long-term storage environment and observe aging changes.

[0134] Test items:

[0135] Anti-aging: Measure the color difference (ΔE) every 24 hours and record the yellowing.

[0136] Lightfastness: The yellowing and fading of the coating were measured after 72 hours to evaluate the anti-aging performance.

[0137] Experimental data:

[0138] Experimental summary:

[0139] Time (hours) Example 1 (ΔE) Comparative Example 2 (ΔE) 0 0 0 24 0.3 1.5 48 0.6 2.8 72 1 4.5

[0140] Comparative Example 2, which did not add antioxidants and UV screeners, had a significantly increased ΔE value after 72 hours, and yellowing and fading were obvious. However, Example 1 showed significant durability in the anti-aging test, with a ΔE value of only 1.0, maintaining good color and structural stability. The experiment showed that the synergistic system of antioxidants and UV screeners effectively reduced the yellowing and embrittlement rate of the reinforcement material under oxidation and UV rays, providing a better choice for the long-term protection of paper cultural relics.

[0141] Comparative experiment 3: Comparison between the existing composite materials without self-repairing microcapsule technology and the technical solution of the present invention

[0142] Purpose:

[0143] Evaluate the role of self-healing microcapsules in reinforced materials to see how they can extend the service life of the material and reduce maintenance requirements.

[0144] Experimental process:

[0145] Material ratio:

[0146] Comparative Example 3: does not contain self-repairing microcapsules, only contains nanocellulose (15%), natural polymer bonding substrate (20%), antioxidant (1%), ultraviolet shielding agent (2%), and other components and processes are consistent with Example 1.

[0147] Example 1: Adding 5% of self-healing microcapsules (polysiloxane, size 0.8 microns).

[0148] Preparation and reinforcement:

[0149] Comparative Example 3 and Example 1 were prepared according to their respective formulations, and three layers of coating were performed according to the steps of Example 1. After drying, the coating was placed in an aging box for 72 hours of aging.

[0150] Slight scratches were applied to the aged coatings to observe the self-healing effect.

[0151] Test items:

[0152] Scratch self-repair test: Scratch the sample surface after 72 hours of aging, and record the time required for self-repair and the repair effect.

[0153] Durability test: Observe the surface smoothness and crack condition after scratch self-repair.

[0154] Experimental data:

[0155] Test items Embodiment 1 (present invention) Comparative Example 3 (without self-repairing microcapsules) Scratch self-repair time 2 hours No self-repair Durability Scratch completely repaired Significant scratches and cracks on the surface

[0156] Experimental summary:

[0157] Comparative Example 3 did not add self-repairing microcapsules, and scratches could not be spontaneously repaired. During the aging process, obvious cracks and damage appeared on the surface. Example 1 completely repaired the scratches within 2 hours, and the surface was smooth and crack-free, demonstrating the effectiveness of self-repairing microcapsules. The experimental results show that self-repairing microcapsules can significantly extend the service life of the reinforcement layer, reduce the number of maintenance times, and are suitable for long-term cultural relics protection.

[0158] Comparative Experiment 4: Comparison between the prior art solution without vacuum infiltration treatment and the technical solution of the present invention

[0159] Purpose:

[0160] Evaluate the effect of vacuum infiltration treatment on material permeability, adhesion and deep reinforcement effect, and verify the role of vacuum infiltration process in improving the stability of reinforced materials.

[0161] Experimental process:

[0162] Material ratio:

[0163] Comparative Example 4: The composite material formulation of Example 1 was used, but vacuum infiltration treatment was not performed, and conventional surface coating methods were adopted.

[0164] Example 1: The composite formula of Example 1 was followed and subjected to 50 kPa vacuum penetration treatment.

[0165] Preparation and reinforcement:

[0166] Comparative Example 4: The material solution was evenly coated on the surface of paper with a thickness of 0.4 microns, and three layers of coating were performed, and each layer was dried naturally.

[0167] Example 1: According to the vacuum infiltration process of Example 1, the material is coated and placed in a vacuum environment to enhance the penetration effect of the reinforcement material.

[0168] Test items:

[0169] Penetration depth test: Observe the paper cross section under a microscope to determine the penetration depth of the reinforcement material.

[0170] Adhesion test: Use a scratch test to measure the adhesion strength of the coating and observe the peeling.

[0171] Experimental data:

[0172] Test items Embodiment 1 (present invention) Comparative Example 4 (No Vacuum Penetration) Penetration depth (μm) 20 5 Adhesion strength (N) 15 8

[0173] Experimental summary:

[0174] The penetration depth of comparative example 4 without vacuum penetration was significantly lower, only 5 microns, and the adhesion strength was 8N, which was prone to peeling. In contrast, Example 1 achieved a deep penetration of 20 microns through vacuum penetration treatment, and the adhesion strength reached 15N. The reinforcement layer was tightly combined with the paper fibers to ensure the stability of the structure. The experimental results show that vacuum penetration can effectively improve the permeability and adhesion of the reinforcement layer, making the composite material more suitable for deep-level cultural relics protection.

[0175] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Biofiber composite material for paper cultural relics reinforcement, characterized in that: The composite material comprises the following components: Nanocellulose, accounting for 5-20% of the total mass of the composite material, and the particle size of the nanocellulose is 20-100 nanometers; A natural polymer bonding substrate, accounting for 10-30% of the total mass of the composite material, wherein the natural polymer bonding substrate comprises a mixture of chitosan and gelatin, and the mass ratio of chitosan to gelatin is 2:1; An antioxidant, accounting for 0.1-2% of the total weight of the composite material, wherein the antioxidant comprises catechin and / or ferulic acid; An ultraviolet shielding agent, accounting for 0.5-5% of the total mass of the composite material, wherein the ultraviolet shielding agent comprises titanium dioxide nanoparticles and lignin; The self-repairing microcapsules account for 1-10% of the total mass of the composite material. The self-repairing microcapsules wrap polysiloxane and the size of the self-repairing microcapsules is 0.5-1 micron.

2. The biofiber composite material for reinforcing paper cultural relics according to claim 1, characterized in that: The mass ratio of catechin to ferulic acid in the antioxidant is 1:1 to 3:

1.

3. The biofiber composite material for reinforcing paper cultural relics according to claim 1, characterized in that: The particle size of the titanium dioxide nanoparticles in the ultraviolet shielding agent is 10-50 nanometers, and the mass percentage of the lignin in the composite material is 0.5-2%.

4. The method for preparing the biofiber composite material for reinforcing paper cultural relics according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) ultrasonically dispersing 5-20% of nanocellulose in deionized water for 15-30 minutes to prepare a nanocellulose dispersion; (2) adding 10-30% chitosan and gelatin in a mass ratio of 2:1 into the nanocellulose dispersion and stirring until it is uniformly dissolved; (3) adding 0.1-2% of an antioxidant and 0.5-5% of an ultraviolet shielding agent to the mixed solution of step (2), and subjecting the mixture to mechanical stirring and ultrasonic treatment for 10 minutes to obtain a uniformly dispersed mixed solution; (4) adding 1-10% of self-repairing microcapsules to the mixed solution of step (3), stirring at a low speed for 5-10 minutes to uniformly disperse the self-repairing microcapsules in the mixed solution, and obtaining a composite material solution; (5) Add an appropriate amount of ethanol or propylene glycol to adjust the viscosity of the mixed solution in step (4) to a fluidity suitable for coating.

5. The method for preparing the biofiber composite material for reinforcing paper cultural relics according to claim 4, characterized in that: In the step (1), the nanocellulose is ultrasonically dispersed in deionized water for 20 minutes at a mass fraction of 5-20%, and the dispersion uniformity is high; the antioxidant in the step (3) is a combination of 0.5% catechin and 0.3% ferulic acid by mass percentage, and the ultraviolet shielding agent is a combination of 1% titanium dioxide and 1% lignin.

6. A method for reinforcing a paper cultural relic, comprising the step of reinforcing the paper cultural relic using the biofiber composite material according to claim 4, the method comprising the following steps: The composite material solution is coated on the surface of paper layer by layer with a thickness of 0.3-0.5 microns to form a multi-layer progressive coating, and each layer is dried at low temperature after coating; Placing the paper artifact in a vacuum environment, wherein the vacuum pressure is controlled at 50-100 kPa, and using a vacuum-assisted infiltration process to allow the composite material solution to infiltrate into the paper structure; Each coating layer is dried at a temperature not exceeding 40°C for 30 minutes to cure the composite material layer by layer to obtain a multi-layer reinforcement effect.

7. The method for reinforcing paper cultural relics according to claim 6, characterized in that: The multi-layer progressive coating includes 3-5 layers of coating, the nanocellulose concentration of the composite material solution in each layer decreases layer by layer, and the outermost layer is a composite material solution with high transparency.

8. The method for reinforcing paper cultural relics according to claim 6, characterized in that: The vacuum-assisted infiltration process includes maintaining a vacuum environment of 50-100 kPa for 5-15 minutes, so that the composite material solution enters the gaps between paper fibers under the action of vacuum to form a tightly combined reinforcement structure.

9. A paper cultural relic reinforcement system according to claim 1 to claim 8, the system comprising the following devices: A biofiber composite material preparation device for preparing a biofiber composite material containing nanocellulose, natural polymer, antioxidant, UV shielding agent and self-repairing microcapsule according to the steps of claims 1 to 4; Environmental control device, used to provide constant temperature conditions of 20-25°C and constant humidity conditions of 50-60% to prevent the paper from being affected by environmental changes during the reinforcement process; A coating device, used to coat the composite material solution on the paper surface layer by layer with a thickness of 0.3-0.5 microns; Vacuum-assisted penetration device, used to place paper artifacts in a vacuum environment of 50-100 kPa to allow the composite material solution to evenly penetrate the paper structure; Low-UV lighting device, used for low-UV lighting of paper artifacts during the reinforcement process.